Exploring Data Engineering Technology for Worker Incentive - Mohd Anuar, Nurulain Syafiqah (IRC, 2020)
Managing large amount of data from various resources that create structured, unstructured and semi-structured is challenging. Especially in manufacturing industry which the sources may come from machine, robots, computer and human. In this paper, we will be focusing on the worker’s incentive management in manufacturing industry which involved Human Resource Management and Production Unit. The aim of this study is to reduce the time taken and tedious incentive management from data engineering workflow technology perspective. The objective of this research firstly, to study the effectiveness of data engineering workflow technology. Secondly, to identify the gaps and redundancy on existing process and operational workflow. Lastly, to develop a system in reducing the gaps and redundancy of the workflow. Thus, data ingestion architecture approach is required integrate data in positive manner to get informative data and better data management.